Invisible murder - Kaaberbøl, Lene (Kaaberbol, Lene. Nina Borg mysteries, 2012)
Red Cross nurse Nina Borg risks her marriage to assist her friend Peter at a camp of mysteriously ill Roma refugee children whose circumstances prove more complicated and dangerous than originally believed.